'Incentivizing Recovery' follow‐up: White paper was a 'first step'. Issue 36 (21st September 2018) - Knopf, Alison
Abstract : Last week's issue featured the announcement of a new payment model for addiction treatment, a combination of capitated and bundled reimbursement that places the treatment provider at risk in the event of repeat admissions. Greg Williams, executive vice president of Facing Addiction with NCADD, described the rationale for the system: Treatment providers should not be paid if patients don't get well. Anne Marie Polak, senior director at Leavitt Partners and in charge of the "Incentivizing Recovery" project the organization is convening, described the basics of how the project works. None of the treatment organizations participated in the project, which resulted in the white paper released Sept. 7 (see ADAW, Sept. 17).